Direct and Indirect Somatic Embryogenesis Induction in Camellia oleifera Abel - Zhang, Ming; Wang, Aibin; Qin, Mou; Qin, Xuejing; Yang, Shiwen; Su, Shuchai; Sun, Yongjiang; Zhang, Lingyun (Frontiers in Plant Science, 2021)
Camellia oleifera Abel. is an important woody oil species; however, the shortage of rapid and industrialized seedling culture is a large constraint on the development of the tea oil industry. Somatic embryogenesis (SE) is one of the main powerful biotechnological tools for plant mass regeneration, but the largely unknown SE in C. oleifera limits the scale production of clonal plants. In this study, we described a high-efficiency SE system via direct and indirect pathways in Camellia oleifera and investigated the effect of genotype, explant age and phytohormones on SE. In the direct pathway, somatic embryos were highly induced from immature seeds 220 days after full blossom, and the development of embryoids was achieved with a combination of 0.19 mg/L 2,4-dichlorophenoxyacetic acid (2,4-D) and 0.05 mg/L thidiazuron (TDZ). In the indirect pathway, embryogenic calli were induced from the same explants in medium containing 1.5 mg/L 2,4-D, while 0.75 mg/L 2,4-D treatment led to high proliferation rates for embryogenic calli. The addition of 0.19 mg/L 2,4-D alone stimulated the production of globular embryos while causing a 75% loss of the induction rate in the heart embryo stage. Upon transfer of the globular embryos to phytohormone-free medium, we obtained an optimal induction efficiency for cotyledons of 62.37%. These data suggest that the subsequent differentiation process after the globular embryo stage is more similar to spontaneous development than phytohormone-driven process in ISE. Mature embryos germinated to produce intact plantlets on half-strength MS basal medium with a regeneration rate of 63.67%. Histological analysis confirmed the vascular bundle isolation of embryoids from the mother tissue. We further studied the different varieties and found that there were no significant genotype differences for SE induction efficiency in C. oleifera. Thus, we established a high-efficiency induction system for direct and indirect somatic embryogenesis in C. oleifera and regenerated intact plantlets via somatic embryogenesis, not organogenesis. Indirect somatic embryogenesis has a more complicated induction and regulatory mechanism than direct somatic embryogenesis. The improved protocol of somatic embryogenesis would benefit mass propagation and genetic manipulation in C. oleifera.